Do circulating neutrophil extracellular traps predict recurrence in early breast cancer? - Martinez-Cannon, Bertha Alejandra; Garcia-Ronquillo, Karen; Rivera-Franco, Monica M.; Leon-Rodriguez, Eucario (Frontiers in Oncology, 2023)
Background Neutrophil extracellular traps (NETs), three-dimensional structures formed by neutrophil enzymes such as neutrophil elastase (NE) and nuclear components (DNA), have been associated with progression and metastasis in breast cancer (BC). Thus, the aim of this study was to evaluate the association of circulating NETs with clinicopathological characteristics and outcomes in localized BC. Methods A prospective cohort included 45 women with newly diagnosed BC. NETs were defined as the presence of NE-DNA complexes in plasma, measured by optical density. Levels of NETs were dichotomized according to the median, as low and high levels of circulating NETs. For this analysis, only women with early BC were included. Results Forty patients were included, 23 (57.5%) patients with low and 17 (42.5%) with high levels of circulating NETs. No associations were found between clinicopathological characteristics and circulating NETs levels. Recurrence (p = 0.75) and site of recurrence (p = 0.25) were not statistically associated with plasma NETs levels. Overall, recurrence-free survival was not statistically different between according to circulating levels of NETs. Conclusions With a short follow-up, our results show that circulating levels of NETs at diagnosis of early BC are not associated with more aggressive clinicopathological tumor characteristics, recurrence, or site of recurrence.